The cybersecurity body of knowledge : the ACM/IEEE/AIS/IFIP recommendations for a complete curriculum in cybersecurity /: the ACM/IEEE/AIS/IFIP recommendations for a complete curriculum in cybersecurity. (2020) - Shoemaker, Dan; Kohnke, Anne; Sigler, Kenneth
No abstract available